KOMUNIKASI MASYARAKAT JEPANG DITINJAU DARI SISI MANAJEMEN PRIVASI KOMUNIKASI (STUDI KASUS PADA MAHASISWA GRADUATE UNIVERSITY FOR ADVANCE STUDIES) - Krisnawati, Vera Eka (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
1. Abstract:The purpose of this research is to describe about communication of Japanese people. Japan has become a tremendous nation in technology. The impacts have both positive and negative sides which create the Japanese people became very cautious about their interaction especially in communication with each other or to foreigners. This study is trying to observe in relation to communiction of Japanese people using a qualitative method and Communication Private Management theory. The subject would be college students at Graduate University for Advanced Studies in Sagamihara, Japan. Communication Private Management theory research about description for the action that people do based on intension, substance, and event that create in their language to communicate with other people or with them selves. The result of this research is interaction between Japanese people and foreigners are possible as long as the ideas of self perception and the relationship with the society reach the accomplishment. Japanese people would be very generous and kind as long as the communication would be clear and good for them.Keywords: Communication Private Management theory (CPM), Japan, Japanese People